Refleksi Sosial dalam Novel Al Baqi Min Zamani Sa`ah Karya Naguib Mahfouz (Kajian Sosiologi Sastra Swingewood): Social Reflection in the Novel Al Baqi Min Zamani Sa`ah by Naguib Mahfouz (Swingewood Sociology of Literature Study) - Adnan Maulana Yusuf; Rohanda Rohanda; Yayan Rahtikawati (Information Technology and Science(ITScience), 2026)
This study analyzes the social reflection in Egyptian society in Naguib Mahfouz's novel Al-Baqi Min Zamani Sa'ah, using Alan Swingewood's sociology of literature approach and Lewis's theory of conflict-causation factors. The method used is a descriptive, qualitative approach, employing note-taking techniques and content analysis of text excerpts representing Egyptian social reality between 1936 and 1979. This study answers two research questions: how are social reflections on history, ideological conflict, and intergenerational conflict represented in the novel, and what factors cause the ideological and intergenerational conflicts it reflects? The study's results reveal three main findings. First, the novel documents the partial and pluralistic social awareness of Egyptian society in its responses to historical events from the 1936 Agreement to the 1979 Camp David Agreement. Second, ideological fragmentation between secular nationalism, political Islam, and leftist groups not only occurs in the public sphere but also penetrates the domestic space of the family as an arena for value struggles. Third, uneven modernization triggers latent but persistent intergenerational tensions in family relations. Leuwis's theory explains these conflicts as being influenced by differences in values ??and beliefs, differing interests, socioeconomic disparities, and limited access to resources. This research confirms that the novel AMZS serves as both a sociohistorical archive and a sociocultural document, capturing the dynamics and social awareness of Egyptian society during four decades of political change.